MINERvA Measurements of Partonic Nuclear Effects with Neutrinos - Norrick A. (2017)
Measurements of the Deep Inelastic Scattering (DIS) neutrino cross-section ratios between Carbon, Iron, and Lead to Scintillator are presented by the MINERvA collaboration. These flux-integrated cross-section ratios are presented as a function of the Bjorken scaling variable x, and as a function of neutrino energy. Events in this sample span the neutrino-energy range of 5-50 GeV. Data is low relative to the GENIE prediction in the nuclear shadowing region, x < 0.1. These results have been published and can be found in Reference [2]. Future measurements using a 6 GeV neutrino beam will also be discussed.